Event-related potentials associated with cognitive control in adolescents exposed to complex childhood trauma - Gabriela M. Marcu; Andreas Müller; Juri (Yury) D. Kropotov (European Journal of Psychotraumatology)
Background: Complex childhood trauma (CCT), characterized by repeated and prolonged exposure to adverse experiences, disrupts cognitive, emotional, and neural development. Adolescence, a critical developmental period, is particularly vulnerable to these effects, with CCT increasing the risk of psychopathologies, including post-traumatic stress disorder (PTSD). Despite this, the neurophysiological underpinnings of trauma-related deficits in cognitive control remain insufficiently explored, particularly in the developing brains of children and adolescents. This study aimed to investigate the neurophysiological markers of cognitive control in adolescents with CCT using event-related potential (ERP) components to propose an electrophysiological phenotype associated with CCT, as a vulnerability for PTSD.Methods: Twenty adolescents with CCT and 40 age- and gender-matched healthy controls performed a cued GO/NOGO task. ERP components – contingent negative variation (CNV), NoGo-N2, and NoGo-P3 – were analysed alongside behavioural measures such as omission and commission errors and reaction time, using a preregistered protocol. Statistical analysis included Mann–Whitney tests and cluster-based permutation tests for ERP comparisons.Results: Adolescents with CCT showed significant impairments in both proactive (reduced CNV amplitudes) and reactive (diminished NoGo-N2 and NoGo-P3 amplitudes) control mechanisms. Behaviourally, the CCT group exhibited higher omission errors and shorter reaction times than controls. Exploratory analysis revealed reduced amplitudes in the visual negativity (VN) component, suggesting disruptions in predictive processing. Latent component analysis identified ERP markers with potential diagnostic utility, linking deficits to key neural circuits associated with cognitive control and predictive processing.Conclusion: Study findings highlight significant impairments in cognitive control mechanisms and disrupted predictive processing in adolescents with CCT, emphasizing the importance of addressing trauma-related neural deficits during adolescence. Given that CCT is a significant risk factor for PTSD, the study provides insights into shared neurobiological pathways, supporting the development of targeted interventions. ERP markers like CNV, NoGo-N2, NoGo-P3, and VN show promise for improving diagnostic precision and monitoring therapeutic outcomes in trauma-exposed youth.